Bloodstream Infections Caused by Klebsiella pneumoniae Carbapenemase–Producing P. aeruginosa Sequence Type 463, Associated With High Mortality Rates in China: A Retrospective Cohort Study - Hu, Hangbin; Zhang, Yan; Zhang, Piaopiao; Wang, Jie; Yuan, Qing; Shi, Weixiao; Zhang, Sheng; Feng, Haiting; Chen, Yunbo; Yu, Meihong; Chen, Hongchao; Jiang, Yan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives Recently, KPC-producing P. aeruginosa has rapidly emerged and expanded in East China. Here we described the clinical impact and characteristics of bloodstream infections (BSIs) from the dominant KPC-producing CRPA belonging to Sequence Type (ST) 463. Methods Retrospective cohort study was performed with CRPA BSI cases from 2019 to 2020 in a hospital in East China. Clinical characteristics, risk factors, and all-course mortality were evaluated. All CRPA isolates had whole-genome sequencing, antimicrobial susceptibility testing, and serum resistance assay. Representative isolates were tested for virulence in a Galleria mellonella infection model. Results Among the 50 CRPA BSI cases, ST463 predominated (48.0%). In multivariate analysis, we found three independent risk factors for fatal outcome: KPC carriage (OR 4.8; CI95% 1.0-23.7; P = 0.05), Pitt bacteremia score (OR 1.3; CI95% 1.0-1.6; P = 0.02), and underlying hematological disease (OR 8.5; CI95% 1.6-46.4; P = 0.01). The baseline clinical variables were not statistically different across STs, however the 28-day mortality was significantly higher in ST463 cases than that in non-ST463 cases (66.7% vs 33.3%, P = 0.03). ExoU and exoS virulence genes coexisted in all ST463 isolates, and the carbapenem resistant gene blaKPC were produced in almost all ST463 isolates, significantly higher than in the non-ST463 group(95.8% vs 7.7%, P<0.001). ST463 CRPA isolates also showed higher resistance rates to antipseudomonal cephalosporins, monobactam, and fluoroquinolones. And ST463 CRPA was confirmed hypervirulence in the larvae model. The genome of one ST463 CRPA strain showed that the blaKPC-2 gene was the sole resistance gene located on a 41,104bp plasmid pZYPA01, carried on a 7-kb composite transposon-like element flanked by two IS26 elements (IS26–Tn3-tnpA–ISKpn27–blaKPC-2–ISKpn6–IS26). Plasmid from various species presented core blaKPC-2 was franked by mobile genetic element ISKpn27 and ISKpn6. Conclusions In the ST463 CRPA BSI cohort, the mortality rates were higher than those in the non-ST463 CRPA BSI. The ST463 CRPA clone coharboring the blaKPC and exoU/exoS genes emerged and spread in East China, which might develop to a new threat in the clinic. Our results suggest that the surveillance of the new high-risk clone, ST463 CRPA, should be strengthened in China, even worldwide in the future.